GENESIS OF CRISIS EVENTS IN DOMESTIC ARTISTIC AND CREATIVE (MUSICAL) PEDAGOGY - Djumaboeva Muqaddas SHavkatovna (Scholar Express Journal, 2021)
The article reveals, as in other spheres of life, the contradiction in pedagogy appears in the form of dialectical unity and interaction of opposites, falling under the principle of the universal interconnection of objects and phenomena of the surrounding world. It is the contradiction that serves in pedagogy as a source of movement, development, renewal of the essential foundations, types and forms of the corresponding activity, while at the same time possessing a pronounced specificity.
Keywords: Genesis; artistic and creative pedagogy; vocal school; education